دراسة مقارنة لبعض عناصر اللياقة البدنية الخاصة والمهارات الأساسية بين خطوط اللعب المختلفة في كرة القدم - MOHAMMED, DINDAR FAIDHI; Nabi, DILKHAS RAMADHAN; HADAD , ARAZ QADER; KHDHR, AHMED ALI (Journal of Duhok University, 2020)
This research aims at identifying the differences between the various playing lines in football regarding some elements of specific physical fitness and basic skills. The study hypothesizes that there are statistical differences of some elements of physical fitness and basic skills among the various playing lines in football. The research has adopted the descriptive approach through comparison to arrive at its findings and conclusions. The sample of the study consists of (25) players, (6) players for each line and it excludes (7) players because of being injured or not completing tests. The sample has been chosen by intentional method and statistical analytical program (SPSS) has been used. The study has arrived at some findings and conclusions, among which are the following: There are significant differences among the players of Dalkurd academy in terms of specific physical features (fitness, the ultimate strength of feet, transitional speed) among the various playing lines. There are no significant differences among the players of Dalkurd academy regarding basic skills (rolling, short passes, close targeting) among the various playing lines. The study has recommended the following: Attention should be paid to elements of specific physical fitness of all playing lines particularly fitness, the ultimate strength of feet, transitional speeds. Attention should be paid to the skillful aspect including all basic skills particularly rolling, short passes and close targeting.